miR-29c-3p downregulation accelerates spinal cord injury progression by targeting BRD4 - Dawei Wang; Xiaona Wang; Yingshuang Wu; Sina Qi; Haifeng Hu; Jifei Guo; Yi Luo (Journal of Orthopaedic Surgery and Research)
Abstract Background Spinal cord injury (SCI) can cause severe motor and sensory deficits below the injury site. Studies have highlighted the multifaceted regulatory roles of miR-29c-3p in neuronal development and function; however, its role in SCI remains unclear. Methods In this research 105 healthy controls and 159 patients with SCI were recruited. The miR-29c-3p and BRD4 levels in serum or cells were estimated by RT-qPCR. The diagnostic performance of miR-29c-3p was assessed by ROC curve. Moreover, cell viability and apoptosis were measured via CCK8 and flow cytometry. The pro-inflammatory cytokines were examined by ELISA assay. The pathological condition of SCI was modeled with LPS-induced PC12 cells. The target relationship between miR-29c-3p and BRD4 was verified by the dual-luciferase reporter assay. Results Serum miR-29c-3p was remarkedly decreased in the SCI population and showed high clinical diagnostic performance. Under pathological conditions, the upregulation of miR-29c-3p effectively reversed the significant reduction in cell viability and the increase in apoptosis rate. Moreover, enhanced pro-inflammatory cytokines including TNF-α, IL-6 and IL-1β were also attenuated by the upregulation of miR-29c-3p. BRD4 was identified as a target of miR-29c-3p and negatively regulated by miR-29c-3p. Conclusions A decrease in miR-29c-3p is a promising diagnostic indicator for SCI, and downregulation of miR-29c-3p accelerates the progression of SCI by targeting BRD4.